The ecology of an endemic and rare species with a fragmented distribution: Cyclamen balearlcum Willk in France - Debussche, M.; Grandjanny, M.; Debussche, G.; Affre, L. (ACTA BOTANICA GALLICA, 1996)
The ecology of rare species is largely unknown. Though informations on the ecology of these species, as well as on their biological traits and genetics, are necessary to achieve their conservation. Ecology of Cyclamen balearicum Willk. in France was studied by analysing a set of 40 phyto-ecological releves. This late successional species grows in France under a mediterranean climate, in shaded situations, in sites characterized by moderate to copious precipitations (650 to 1800 mm per year) and frosts occurring each year commonly (mean of the minima of the coldest month from - 0,7 degrees C to + 0,7 degrees C), steep relief and north aspect, stony calcareous soils with blocks, important cover of evergreen woody plants, small number of therophytes, very Low human impact. Quercus ilex L. and Buxus sempervirens L. are very often the dominant tree and shrub species In these sites. Two kinds of habitat were distinguished. They mainly differ on geomorphological features, vegetation height and floristic composition. Ecological patterns were discussed in relation with decisive factors such as shade, frost and drainage, and human impacts. The farm or rarity showed by the species in France was discussed according to the criteria proposed by Rabinowitz. As numerous endemic species with narrow distribution, Cyclamen balearicum Willk. has in France a restricted habitat, but where it grows it is sometimes abundant.
The following values have no corresponding Zotero field: pub-location: RUE J B CLEMENT, 92296 CHATENAY-MALABRY CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: cyclamen balearicum Willk; ecology; endemic species France; habitat specificity; Mediterranean Region; rare species

BIRD-DISPERSED SEED RAIN AND SEEDLING ESTABLISHMENT IN PATCHY MEDITERRANEAN VEGETATION - Debussche, M.; Isenmann, P. (OIKOS, 1994)
The composition and spatial patterns of the seed rain produced by bird dispersers and of the seedlings of fleshy-fruited plants have been studied in patchy Mediterranean vegetation in southern France. The seeds of fleshy-fruited plants were collected in seed traps during a 17-month period (1981-1983) and the fecal samples of bird dispersers mist-netted on the same 2.5-ha site over a 25-month period (1981-1984) were analysed. The locations of the 5 sets of seed traps and the 6 mist-nets were chosen in order to take into account the various plant communities and the successional gradient from old fields to Quercus ilex coppice. Seedling establishment of fleshy-fruited plants was censused in 1983 adjacent to the seed traps. In 1992 seedlings were again censused in the open coppice and in the old fields. The seeds of 38 fleshy-fruited plants were collected, including 13 alien and cultivated species. Among them, 25 species were dispersed by Sylvia atricapilla, which dispersed the most diverse and mixed seed rain of the various bird dispersers. Species richness of the seed rain increased log-linearly with seed density, ranging from 3 to 21 species per 0.25 m2. Seed density was very heterogeneous in space. The maximum density of seeds was observed under the canopy of isolated trees and saplings in the old fields (up to 829 per 0.25 m2) which are the favoured perching places for the dispersers. Minimum density was observed in the same old fields outside the canopy of these same trees and saplings (down to 12 per 0.25 m2). In the Quercus ilex coppice, the higher the canopy, the higher the seed density. Dispersal was a short distance process. A large majority of the seeds of Pyracantha coccinea and Sambucus nigra were dispersed by birds less than 100 m from the maternal plant. However, a dispersal distance of > 300 m was observed for a seed of Ligustrum vulgare, In 1983 the < 1 yr-old seedlings of 17 fleshy-fruited plants, including only one alien species, and the 1-2 yr-old seedlings of 7 native species were censused. Though important components of the seed rain, no 1-2 yr-old seedlings of several alien (e.g. Pyracantha coccinea) or native (e.g. Rhus coriaria) species were observed in the studied vegetation. Seedlings were more numerous under tree cover than in the coppice clearings. In the old fields, < 1 yr-old seedlings were more numerous under the canopy than in open areas. No such difference was observed under saplings in 1983 and very few seedlings were observed in the old fields. The 1992 census suggested that the positive role of the cover of pioneer plants on seedling establishment progressively increased with successional development. This is probably due to an increase in the nurse effect and a decrease in the herbaceous cover under the canopy. It is suggested that. in old fields. the establishment of fleshy-fruited plants is favoured when seeds are deposited under pioneer woody plants rather than in open areas. The bird dispersers thus trigger dynamic processes initiated by the pioneer woody plants in Mediterranean old field succession. More generally, dispersal of fleshy-fruited plants by birds is more significant in the central stages of succession gradient than it is in open herbaceous communities and in dense forest when both have an homogeneous structure.
APSAPSThe following values have no corresponding Zotero field: pub-location: 35 NORRE SOGADE, PO BOX 2148, DK-1016 COPENHAGEN, DENMARK publisher: MUNKSGAARD INT PUBL LTD
Keywords: bird dispersers; fleshy-fruited; France; Mediterranean; Quercus ilex; seedlings

A MEDITERRANEAN BIRD DISPERSER ASSEMBLAGE - COMPOSITION AND PHENOLOGY IN RELATION TO FRUIT AVAILABILITY - Debussche, M.; Isenmann, P. (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1992)
This study deals with a fleshy-fruited plant-bird dispersal system at a site in Mediterranean France, characterized by Quercus ilex coppices, shrublands and old fields. Among the 19 bird dispersers recorded, 14 were of small size (< 25 g), with Sylvia atricapilla, Erithacus rubecula and S. melanocephala accounting for 86.6 % of those caught in mist nets. The importance of small-sized dispersers seems to characterize the Mediterranean shrublands and evergreen woodlands in the whole of the temperate systems. The highest numbers of dispersers occurred from October to January. The seeds of 38 fleshy-fuited plants (native, cultivated and alien) were collected in seed traps. Seed rain occurred throughout the year except in May, with a maximum fruiting period extending from September to early December and the greatest number of native species being dispersed in October. When we compare our data to those collected in Spain, England and Sweden a shift of the peak of fruit availability in relation to latitude (the higher the latitude the earlier the peak) is very likely in Europe. Such a shift is obvious in the United States. We suggest that 1) this shift is the result of climatic constraints on plants rather than that of the selective pressures of dispersers, and 2) that the coincidence between high fruit availability and dispersers' abundance can simply result from the opportunist behaviour of frugivorous birds.
Keys: APSKeys: APSThe following values have no corresponding Zotero field: pub-location: 57 RUE CUVIER, 75005 PARIS 5, FRANCE publisher: SOC NATL PROTECTION NATURE ACCLIMATATION FRANCE
Keywords: birds; dispersal system; evergreen woodlands; Mediterranean; Quercus ilex